Learning English in the AI Era: Challenges and Opportunities for Today's Higher Students - Alias, Hamzah (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The rapid development of artificial intelligence (AI) has brought significant transformations to the educational landscape, including English language learning at the tertiary level. This study aims to explore the challenges and opportunities of using AI technology in the learning process for students of the English Language Education program at As'adiyah Islamic University, Sengkang. The main issue raised is the gap between easy access to AI tools (such as ChatGPT, QuillBot, or Grammarly) and the risk of reducing critical thinking skills and originality in students' work. The research method used is a descriptive qualitative approach. Data were collected through observations and in-depth interviews with English Language Education students at As'adiyah Islamic University, Sengkang, to understand their perceptions and experiences in integrating AI into academic assignments. The results show that AI offers significant opportunities to improve learning efficiency, such as instant grammar correction and the provision of varied learning resources. However, the main challenges faced are over-reliance on technology that has the potential to erode independent writing skills and ethical challenges related to academic integrity. This research is meant to help study program managers and teachers assess how to create flexible English learning strategies, using AI as a helpful tool while still focusing on building real language skills.